Impact of Employees’ Turnover on the Performance of Five Star Hotels of Kathmandu - Shrestha, Bijaya; Thapa, Roshan (Kathford Journal of Engineering and Management, 2023)
This study examined the Impact of Employee Turnover on the Performance of Five five-star hotels. Data was collected from the 120 hotel employees from six hotels in Kathmandu using the questionnaire. The employees were randomly sampled. Jamovi was used to run the analysis. While collecting the data among the respondents, 91 (75.8%) were Male, and 29 (24.2%) were female. Likewise, 64 (53.3%) were staff, 36 (30.0%) were supervisors, and 20 (16.7%) were heads of departments. Out of 120 respondents, 51 respondents (42.5%) had worked in the respective hotel for <5 years, followed by those who had worked for 6–10 years were 22 respondents (18.3%), while 12 respondents (10.0%) had worked for 11–15 years and 35 respondents (29.2%) had worked for more than 16 years. Employee turnover has highly affected the Organizational performance of the hotel. So, for that reason, the hotel has used various strategies related to employee retention. Likely examining employee turnover and its impact on organizational performance, the researcher uses correlation and regression, which shows the negative impact on organizational performance.